OXIDATIVE-NUCLEOPHILIC SYSTEMS FOR DECOMPOSITION OF TOXIC SUBSTANCES - ВАХІТОВА, Л. М.; ТАРАН, Н. А.; КОРОТКІХ, М. І.; ВАХІТОВ, Р. А.; БЕССАРАБОВ, В. І.; ПОПОВ, А. Ф. (Technologies and Engineering, 2023)
Purpose. To investigate the kinetics of nucleophilic decomposition of paraoxone by peroxide anion and oxidation of methylphenyl sulfide by hydrogen peroxide in water/alcohol, water/alcohol/detergent and “oil-in-water” microemulsions in the presence of ammonium bicarbonate and boric acid. Methodology. The reactions of nucleophilic substitution of paraoxone and oxidation of methylphenyl sulfide with hydrogen peroxide in nanoscale aqueous-organic systems (water-alcohol, water-alcohol-detergent, “oil-in-water” microemulsion) were chosen as model systems. Paraoxon and methylphenyl sulfide are used as imitators of warfare agents with nerve and blistering effects. Three types of detergents were used to form detergent mixtures and microemulsions: cationic – cetylpyridinium chloride, anionic – sodium dodecyl sulfate, and neutral – 4-(1,1,3,3-tetramethylbutyl)-phenylpolyethylene glycol. Ammonium bicarbonate and boric acid were used as activators. The nucleophilic substitution of paraoxone was monitored spectrophotometrically at λ = 405 nm by the change in the absorbance of 4-nitrophenolate ion over time in the concentration conditions [HOO- ]>>[paraoxone]. Oxidation was monitored by the decrease in methylphenyl sulfide absorbance over time at λ = 250 nm. under the condition [H2O2]>>[ methylphenyl sulfide]. Findings. The kinetic parameters of the nucleophilic decomposition of paraoxone by hydrogen peroxide anion and the activated oxidation of methylphenyl sulfide by hydrogen peroxide in an “oil-in-water” microemulsion in the presence of ammonium bicarbonate and boric acid have been determined. It was found that in the microemulsion of water:ethylene glycol (4:1)/alcohol/hexane/detergent composition, the substrate binding constant increases 3–5 times compared to the same value in water-alcohol detergent and micellar solutions. The reactivity of hydrogen peroxide as an oxidant in its neutral form and as a nucleophilic reagent in the form of peroxide anion in the presence and absence of ammonium hydrogen carbonate and boric acid was compared. It was found that the rate of nucleophilic substitution in paraoxone and oxidation of methylphenyl sulfide decreases in an aqueous-alcohol medium, regardless of the alcohol chosen. The addition of detergents to the water-alcohol medium increases the rate of catalysed decomposition of methylphenyl sulfide by oxidative mechanisms by almost 10 times in the presence of cationic cetylpyridinium chloride and 5 times in the presence of neutral 4-(1,1,3,3-tetramethylbutyl)-phenylpolyethylene glycol and anine sodium dodecyl sulfate. At the same time, the acceleration of nucleophilic decomposition of paraoxone was observed, which suggests the dual oxidative-nucleophilic nature of peroxycarbonate and peroxoborate anions. The high reactivity of anions and oxidants in microemulsions has been demonstrated, which, together with the values of the binding constants of both substrates, allows us to consider microemulsion media of the selected formulation as effective degassers and solubilisers of hydrophobic poisonous substances. The results obtained allow us to state that microemulsions containing hydrogen peroxide, cationic detergent and activator can be considered as promising components of decontamination agents for the destruction of ecotoxic compounds by the oxidative-nucleophilic mechanism. The results obtained allow us to state that microemulsions containing hydrogen peroxide, cationic detergent and activator can be considered as promising components of decontamination agents for the destruction of ecotoxic compounds by the oxidative-nucleophilic mechanism. Originality. The formulation of a microemulsion reaction medium with high solubilizing properties was developed for the simultaneous nucleophilic decomposition of paraoxon by peroxide anion and oxidation of methylphenyl sulfid by hydrogen peroxide at high rates. Practical value. The investigated microemulsion can be used as a basis for decontamination formulations to remediate the effects of contamination with chemical weapons components of blistering and nerve effects.